Characterization and optimization of metal and metal oxide thin films fabricated by high-pressure magnetron sputtering deposition technique - Nayan, Nafarizal (2011)
Thin film technology is now a sophisticated and advanced technology. Thin film is used to fabricate many products such as ultra large scale integrated (ULSI) circuit, sensor devices, optical films and protective coating. The applications of thin films is depend on film properties such as film thickness, crystality, morphology, strength and composition. One of the most well known technique for thin film deposition is magnetron sputtering deposition. Basically, the properties of thin film deposited by magnetron sputtering is controlled by the discharge power, gas pressure, gases ratio and substrate temperature. The objective of this study is to investigate the influence of deposition conditions to properties of metal and metal oxide thin films. Zinc oxide thin-film is one of the most studied thin films. The properties of zinc oxide thin films deposited by radio frequency magnetron sputtering are strongly dependent on the sputtering conditions. In order to understand the chemical element and to identifying sputtered neutral particles under ion irradiation, optical emission spectroscopy (OES) analysis measurement have been carried in the present work. The main objective of this project is to study changes in emission as the oxygen gas in introduced. In addition, the influence of working pressure and discharge power toward the optical emission of reactive Zn sputtering plasma were measured. We found that Zn and Ar emission increased with the discharge power. This is due to the enhancement of ionic species at higher discharge power where it increases the sputtering process of Zn target. The similar results were found at Ti plasma using the Ti as sputter target. Finally, in the present work we have proved the optimum condition for oxide thin film deposition where the oxygen ratio should be more than 10%. To our knowledge, this is the first time that this phenomenon was observed and we have presented to international journal and conferences.